Exploring Educational Insights: An In-depth Analysis of Al-Quran Interpretation of the Fasting Verse for Contemporary Islamic Pedagogy - Lidya Ningsih; Laud Pulungan; Bariqy; Harun Al-Rasyid (Yayasan Salam Cerdas Al-Fattah, 2023)
This article aims to explore educational insights with an in-depth analysis of the interpretation of the Koran regarding fasting verses, the fasting verses used, namely QS al-Baqarah verses 183 to 187. In this article the thematic method is used, namely the method used to search for themes. -related themes in the Koran with the correct steps in it, so that in searching the verses it is connected to a complete understanding of the verses that talk about fasting. The findings explain that contemporary Islamic education utilizes these verses as a basis for forming individuals who not only know religious teachings, but are also able to apply moral, ethical and spiritual values in everyday life. Verses 183-187 of Surah Al-Baqarah provide a strong foundation in forming character and an attitude of piety, creating individuals who are tough, responsible and have a deep understanding of Islamic teachings. In conclusion, contemporary Islamic education must be able to combine the fundamental values contained in these verses, involving spiritual, moral, ethical and inclusive aspects in the learning approach.